1973
DOI: 10.1038/sc.1973.14
|View full text |Cite
|
Sign up to set email alerts
|

A new programme of sex education and counselling for spinal cord injured adults and health care professionals

Abstract: THROUGHOUT the world today men and women with traumatic paraplegia and quadriplegia are making increased demands on the health care system to do more than simply manage them through their immediate post injury period. They require workable solutions to the totality of psycho-social problems inherent in a continued state of disability. Yet, Professor Timothy J. Nugent, past President of the National Paraplegia Foundation (I97I), pointed out that many of the as sumptions of the past and some of the advice given … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1976
1976
1991
1991

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…Little is known of the psychological impact of sexual dysfunctions. Some commentators have suggested that patients are more concerned about these than about any other aspect of their disability (Bloom, 1974;Breslin, 1971;Cole et al, 1973), but this may overstate the case. In one study paraplegics rated sex the least of the major functional losses resulting from their injury; 52 per cent thought the loss of the use of their legs the most important, 35 per cent the loss of control over bowel or bladder, and only 13 per cent the loss of sexual functioning (Hanson and Franklin, 1976).…”
Section: Sexual Implicationsmentioning
confidence: 99%
“…Little is known of the psychological impact of sexual dysfunctions. Some commentators have suggested that patients are more concerned about these than about any other aspect of their disability (Bloom, 1974;Breslin, 1971;Cole et al, 1973), but this may overstate the case. In one study paraplegics rated sex the least of the major functional losses resulting from their injury; 52 per cent thought the loss of the use of their legs the most important, 35 per cent the loss of control over bowel or bladder, and only 13 per cent the loss of sexual functioning (Hanson and Franklin, 1976).…”
Section: Sexual Implicationsmentioning
confidence: 99%
“…Among the exceptions are reports by Cole (1973) and his associates describing the Disability Sexual Attitude Reassessment Program at the University of Minnesota and reports by Romano and Lassiter (1972) and Eisenberg and Rustad (1976) describing programs at the University of Michigan and the Cleveland Veterans Hospital, respectively (Cole, 1973;Romano and Lassiter, 1972;Eisenberg and Rustad, 1976). Even more rare are published data on the effectiveness of sexual adjustment 14 counseling programs.…”
Section: Mpmentioning
confidence: 99%
“…The litera ture (Brockway, Green and Kanter, 1978;Cole, 1973;Mayers, 1978) suggests that special training in social techniques can prevent painful ineptitudes and lead to a deeper realization of constructive social rela tionships. Participation in groups of people at similar adjustment states is helpful.…”
Section: Mpmentioning
confidence: 99%
See 2 more Smart Citations